Sanitation and Hygiene Practices in Canteens Around the University of Mataram - Bachmida, Elya Antariksana; Handayani, Baiq Rien; Werdiningsih, Wiharyani; Sinaga, Yesica Marcelina Romauli; Rahayu, Tri Isti (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Food safety is a crucial aspect in maintaining public health, particularly in higher education environments where campus canteens serve as the main providers of food and beverages for students, lecturers, and staff. The proper implementation of hygiene and sanitation practices is one of the key efforts to ensure food safety. This study aims to provide an overview of the knowledge and application of hygiene and sanitation practices among food handlers as a strategic approach to supporting food safety in canteens around the University of Mataram. This research employed a descriptive cross-sectional design using a survey method involving all canteens operating within the campus area. Data were collected through questionnaires and direct observations to assess the knowledge and implementation of hygiene and sanitation practices by canteen managers. Data analysis was carried out using percentage tabulations for each observed aspect. The results showed that most food handlers demonstrated good knowledge of canteen hygiene and sanitation, reaching 73.68%. Compliance with hygiene and sanitation principles in terms of canteen building conditions and personal hygiene of food handlers was categorized as adequate, with a percentage of 77.63% each. Meanwhile, aspects of sanitation facilities and food as well as equipment management were categorized as good, with percentages of 84.2% and 88.60%, respectively. In conclusion, food handlers generally possessed sufficient knowledge and compliance with hygiene and sanitation principles, although improvements are needed in several indicators to support the achievement of optimal food safety for the academic community. Keywords: Food safety, hygiene and sanitation, canteen, knowledge